Penilaian Kinerja Guru Dan Pengembangan Keprofesian Berkelanjutan - Norlela Norlela; Musyarapah Musyarapah (Departement of Mathematics Education, 2024)
This study aims to: To analyze and find out how the Planning, Implementation and Evaluation of Sustainable Professional Development (PKB) for Teachers at Mis Annur Palangka Raya. This research uses a qualitative descriptive approach with a case study method. The subjects in this study were school principals, teachers and education personnel. Collecting data using the method of observation, interviews, and documentation. The techniques used in conducting data analysis are data reduction, data presentation, and conclusion drawing. The validity of the data used to explain the data using triangulation of sources. The results showed that the PKB planning for teachers in these schools adjusted to the conditions and needs of the teachers based on teacher self-evaluation. The implementation of PKB for teachers in these schools consists of elements of self-development activities and innovative work, which can improve and develop teacher competence and professionalism that have an impact on education services at Mis Annur Palangka Raya. The forms of PKB implementation at Mis Annur Palangka Raya are education and training, PKB evaluations for teachers at Mis Annur Palangka Raya are carried out through teacher self-evaluation activities which are used as the basis for further PKB planning.